2016
DOI: 10.1158/1078-0432.ccr-15-0780
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hepatitis Promotes Hepatocellular Carcinoma Recurrence via NF-κB Pathway-Mediated Epithelial–Mesenchymal Transition after Resection

Abstract: Purpose Surgical resection is considered as a curative treatment modality for hepatocellular carcinoma (HCC); however, the incidence of postoperative tumor recurrence is high, leading to worse patient survival. Persistent hepatitis (inflammation) is one of risk factors of tumor recurrence after surgical resection. The aim of this study is to investigate the underlying mechanisms linking liver inflammation to HCC progression. Experimental Design In this study, we used a cytokine array to identify important cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…We have verified that MANF suppresses inflammation and EMT and thereby inhibits invasion and metastases in HCC. It was reported that activation of the NF‐κB signal pathway enhances inflammation and EMT of hepatocytes . Our previous study also showed that MANF inhibits NF‐κB transcriptional activity by binding to the DNA‐binding domain of p65 in nuclei .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…We have verified that MANF suppresses inflammation and EMT and thereby inhibits invasion and metastases in HCC. It was reported that activation of the NF‐κB signal pathway enhances inflammation and EMT of hepatocytes . Our previous study also showed that MANF inhibits NF‐κB transcriptional activity by binding to the DNA‐binding domain of p65 in nuclei .…”
Section: Resultsmentioning
confidence: 78%
“…The results indicate that MANF can suppress hepatocyte EMT during HCC progression. Recently, it was reported that p65 overexpression in the hepatoma cell lines decreases E‐cadherin and increases vimentin level . These findings suggest that activation of the NF‐κB pathway promotes hepatocyte EMT.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple cytokines, including IFN-γ, C-C motif chemokine ligand 1 (CCL1), IL-6, macrophage colony-stimulating factor (M-CSF), chemokine (C-X-C motif) ligand 9 (CXCL9), CCL3, TNF-α, TNF-β, and platelet-derived growth factor-BB (PDGF-BB), are elevated in HCC patients with severe hepatitis and correlated with poor prognosis (21). Among them, IL-6 and TNF-α/β markedly enhanced the levels of exogenous PD-L1 protein expression in FLAG-PD-L1 WT-Hep 3B and WT-SK-HEP-1 cells ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The brain was removed, and the cerebellum was isolated, fixed in 10% formalin, and embedded in paraffin. Five-micron-thick sections were cut and subjected to hematoxylin-eosin (H&E) and immunohistochemical staining as previously described (20). Immunohistochemistry was also performed using tissue arrays of clinical MBs (Alenabio; Cat.…”
Section: Histological and Immunohistochemical Stainingmentioning
confidence: 99%